2019
DOI: 10.1159/000503298
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Risk of Polypharmacy among Community-Dwelling, Elderly Kuwaiti Patients

Abstract: Objectives: To estimate the prevalence of polypharmacy in community-dwelling, older Kuwaiti patients, describe the number and types of drugs used, and identify risk factors associated with polypharmacy. Subjects and Methods: This was a descriptive cross-sectional questionnaire-based survey in which we interviewed 500 community-dwelling Kuwaiti adults over 65 years of age. The data collection occurred during a 4-month period from March to July 2017. Results: Fifty-two percent (n = 260) of the patients were male… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 24 publications
2
14
1
Order By: Relevance
“…Three medications on this list (pantoprazole, rabeprazole, and esomeprazole) reduce gastric acid and are indicated for the treatment of conditions such as GERD and peptic ulcers. These are in line with other studies that have reported associations between polypharmacy and common comorbidities in the elderly [10,11,13,31,32].…”
Section: Plos Onesupporting
confidence: 92%
See 1 more Smart Citation
“…Three medications on this list (pantoprazole, rabeprazole, and esomeprazole) reduce gastric acid and are indicated for the treatment of conditions such as GERD and peptic ulcers. These are in line with other studies that have reported associations between polypharmacy and common comorbidities in the elderly [10,11,13,31,32].…”
Section: Plos Onesupporting
confidence: 92%
“…A recent study conducted in Saudi Arabia among a sample of 3009 older adults found that 55% of them were exposed to polypharmacy [30]. Also, a study in Kuwait showed that more than 60% of the older adults had polypharmacy [31]. In addition, a study in Italy reported that the prevalence of polypharmacy among a national sample of elderly individuals was 40% [10], while a study in Sweden was 44.0% [17].…”
Section: Discussionmentioning
confidence: 99%
“…The studies conducted in different countries such as Saudi Arabia 22 ,Oman 23 , Brazil 24 , and England 25 also showed that gender had no significant impact on polypharmacy. However, research conducted in Kuwait showed significant relation of gender with polypharmacy 26 . Such discrepancy in the output with the demographic characteristics might be one of the beauties of epidemiologic research with a diverse population.…”
Section: Discussionmentioning
confidence: 95%
“…However, research conducted in Kuwait showed significant relation of gender with polypharmacy. 26 Such discrepancy in the output with the demographic characteristics might be one of the beauties of epidemiologic research with a diverse population. The study also reported that education beyond primary education significantly decreased polypharmacy as the case in the present study i.e, the lower the education, the higher was the incidence of polypharmacy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation